A 15-Year Study of Trends in Authorship by Gender in Two U.S. Obstetrics and Gynecology Journals. Issue 4 (April 2018) - Metheny, William P.; Jagadish, Mayuri; Heidel, R. Eric
Abstract : OBJECTIVE: To assess whether there was a significant trend in the number of women as first, last, and coauthors in two U.S. journals of obstetrics and gynecology over the past 15 years and to assess whether this publication rate was commensurate with the percentage of women in the academic specialty. METHODS: This retrospective study identified the gender of first and last authors of original research articles for the years 2000, 2005, 2010, and 2015. We determined trends in publication rates of authorship and coauthorship by pairing the gender of the first and last authors. We selected a subset of the data to compare the percentages of women authors with MDs at U.S. academic institutions with the nationally reported percentages of women faculty in the specialty. RESULTS: The journals yielded 2, 699 articles for analysis. The percentage of articles written by women as first authors increased from 37% in 2000 to 71% in 2015 and, as last authors, increased from 26% in 2000 to 49% in 2015. Paired as coauthors, women published at a rate of 11% in 2000 to 38% in 2015. The analysis of a subset of 1, 621 articles showed that as first authors, women published at a rate equal to or above the percentage of women in academics, but as last authors published fewer articles than expected. CONCLUSION: Women published more articles over time, kept pace or exceeded their faculty percentages as first authors, lagged behind these percentages as last authors, and as coauthors eventually surpassed the publication rate of male coauthors. Abstract : Women keep pace or exceed their faculty percentages as first authors but lag behind these percentages as last authors of original research articles over time.